KEPASTIAN HUKUM TINDAK PIDANA ABORSI PASCA PEMBERLAKUAN KUHP NASIONAL - Awanadi, I Gusti Agung Virlan; I Putu Edi Rusmana; Kadek Indra Dewan Tara (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
The enactment of the National Criminal Code through Law Number 1 of 2023 aims to achieve codification and legal certainty within the Indonesian criminal law system, including the regulation of abortion as a criminal offense. Nevertheless, normative issues remain, particularly concerning the legal status and protection of the fetus as the object of the abortion offense. This study aims to analyze the regulation of abortion crimes following the implementation of the National Criminal Code from the perspective of legal certainty, as well as to examine the implications of the unclear legal status of the fetus on criminal liability and law enforcement practices. This research employs a normative legal research method using statutory and conceptual approaches. The findings indicate that the National Criminal Code has not explicitly defined the legal status of the fetus, nor has it clearly regulated its relationship with the prevailing Health Law. This situation results in uncertainty regarding the limits of criminal liability and creates the potential for divergent interpretations in law enforcement practice. Therefore, normative clarification regarding the legal status of the fetus in the regulation of abortion crimes is necessary to ensure consistent legal certainty following the enactment of the National Criminal Code.